A Look at Violence Against Women in Maceió and Alagoas (Brazil) - Andrade Martins, Rubens; Manzini, Ana Paula Moura; Bacha, Elizabeth (Advances in Social Sciences Research Journal, 2023)
Violence against women can be understood as a form of restriction of their freedom, autonomy, and self-determination, and can be presented in the following types of violence: physical, psychological, sexual, property, and moral. The World Health Organization (WHO) estimates that approximately one in three women in the Americas suffer sexual and/or physical violence. This research focuses on this subject, which is so dear and topical - even though it has been around for thousands of years - by analyzing data on violence against women in Maceió and Alagoas (Brazil), comparing the results, investigating socio-demographic characteristics, observing risk factors and also scrutinizing how this woman-victim is approached. An analysis of the data obtained showed that there were 7,078 notifications of cases of violence against women in the state of Alagoas in 2022. Of those notifications, 36.3% were situations of domestic violence, 62.15% of the victims were pardas (black), 44.5% were aged between 35 and 64, 50.32% had suffered moral and psychological violence and 41.1% involved women living in the capital, Maceió. Concerning Maceió, the results were very similar to those of Alagoas and the neighborhoods with the highest number of records were Benedito Bentes (11.74%), Cidade Universitária (11.05%) and Tabuleiro do Martins (7.55%), allowing us to conclude the presence of a pattern of violence against women in outskirts locations. Due to the seriousness of the physical, emotional, and psychological consequences, this panorama and problem should be a constant focus of debate and research in a country that has exorbitant rates of violence against women.